Studies on the preservation of Boar Semen in various extenders - Vijaya Kumaran (Department of Animal Reproduction, College of Veterinary and Animal Sciences, 1977)
With the ultimate object of evolving a suitable extender for boar semen 72 ejaculates from six boars selected at random from University Pig Breeding Farm, Mannuthy were used for the preservation studies. Six diluents viz., Egg yolk – glucose – citrate, 111ini variable temperature diluent, Coconut milk extender, Kiew – 1, Kiew – 11 and Glucose – glycine – EDTA – bicarbonate – citrate diluent were used to study the keeping quality of boar semen at two temperatures of storage ( 150 and 50C). The highest percentage of progressively motile sperms was observed in glucose – clycine – EDTA – bicarbonate – citrate, Kiew – 11 and Kiew – 1 extenders. At 150 C semen could be stored in these extenders upto 60 hours with good motility. Coconut milk extender proved to be least suitable for the preservation of boar semen both at 150 and 50 C of storage. Progressive motility in all the diluents was higher at 150 C than at 50 C.